Physiological Profiling of Embryos and Dormant Seeds in Two Arabidopsis Accessions Reveals a Metabolic Switch in Carbon Reserve Accumulation - Moreno Curtidor, Catalina; Annunziata, Maria Grazia; Gupta, Saurabh; Apelt, Federico; Richard, Sarah Isabel; Kragler, Friedrich; Mueller-Roeber, Bernd; Olas, Justyna Jadwiga (Frontiers in Plant Science, 2020)
In flowering plants, sugars act as carbon sources providing energy for developing embryos and seeds. Although most studies focus on carbon metabolism in whole seeds, knowledge about how particular sugars contribute to the developmental transitions during embryogenesis is scarce. To develop a quantitative understanding of how carbon composition changes during embryo development, and to determine how sugar status contributes to final seed or embryo size, we performed metabolic profiling of hand-dissected embryos at late torpedo and mature stages, and dormant seeds, in two Arabidopsis thaliana accessions with medium (Col-0) and large (Bur-0) seed size, respectively. Our results show that, in both accessions, metabolite profiles of embryos largely differ from those of dormant seeds. We found that developmental transitions from torpedo to mature embryos, and further to dormant seeds, are associated with major metabolic switches in carbon reserve accumulation. While glucose, sucrose, and starch predominantly accumulated during seed dormancy, fructose levels were strongly elevated in mature embryos. Interestingly, Bur-0 seeds contain larger mature embryos than Col-0 seeds. Fructose and starch accumulated to significantly higher levels in mature Bur-0 than Col-0 embryos, suggesting they contribute to the enlarged mature Bur-0 embryos. Furthermore, we found that Bur-0 embryos accumulated a higher level of sucrose compared to hexose sugars and that changes in sucrose metabolism are mediated by SUCROSE SYNTHASE (SUS), with SUS genes acting non-redundantly and in a tissue-specific manner to utilize sucrose during late embryogenesis.